2016
DOI: 10.1051/swsc/2016023
|View full text |Cite
|
Sign up to set email alerts
|

An empirical model of ionospheric total electron content (TEC) near the crest of the equatorial ionization anomaly (EIA)

Abstract: We present a geomagnetic quiet time (Dst > À50 nT) empirical model of ionospheric total electron content (TEC) for the northern equatorial ionization anomaly (EIA) crest over Calcutta, India. The model is based on the 1980-1990 TEC measurements from the geostationary Engineering Test Satellite-2 (ETS-2) at the Haringhata (University of Calcutta, India: 22.58°N, 88.38°E geographic; 12.09°N, 160.46°E geomagnetic) ionospheric field station using the technique of Faraday rotation of plane polarized VHF (136.11 MHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 58 publications
2
28
0
Order By: Relevance
“…TEC is defined as the total number of free thermal electrons present in a column of one meter squared cross section along a path between a radio transmitter and a receiver. This is an important ionospheric state parameter (see Browne et al 1956;Evans 1956;Chakraborty & Hajra 2008;Hajra 2012;Hajra et al 2016a, and references therein). While large latitudinal/longitudinal variations were observed, peak TEC increases varied around 80-100 per cent during the CIRs.…”
Section: What Is the Cometary Plasma Response To The Cir Impact?mentioning
confidence: 99%
“…TEC is defined as the total number of free thermal electrons present in a column of one meter squared cross section along a path between a radio transmitter and a receiver. This is an important ionospheric state parameter (see Browne et al 1956;Evans 1956;Chakraborty & Hajra 2008;Hajra 2012;Hajra et al 2016a, and references therein). While large latitudinal/longitudinal variations were observed, peak TEC increases varied around 80-100 per cent during the CIRs.…”
Section: What Is the Cometary Plasma Response To The Cir Impact?mentioning
confidence: 99%
“…Huang et al [8] created a one-hour ionospheric TEC prediction model for a single station by using Back Propagation (BP) artificial neural network algorithm optimized by a genetic algorithm. Hajra et al [9] developed a single-station ionospheric TEC empirical model using TEC observations over the Calcutta station in India from 1980 to 1990. Jakowski [10] suggested an empirical ionospheric TEC model NTCM-EU suitable for Europe by using the non-linear least squares method.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, EOF analysis was used for the first time to model TEC during geomagnetic storms, and it was found that modeling results agree with observed TEC quite well for storms with nonsignificant ionospheric response while positive and negative storm responses were not sufficiently captured (Uwamahoro & Habarulema, 2015). Multiregression analysis-based methods have been developed and applied to ionospheric modeling during geomagnetically quiet and disturbed conditions, and results agree with observations quite well (Feng et al, 2016;Hajra et al, 2016;Kutiev & Muhtarov, 2001, 2003Li et al, 2016;Mukhtarov et al, 2013). However, the failure to accurately capture positive and negative ionospheric responses was reported for some geomagnetic storms considered for validation (e.g., Mukhtarov et al, 2013).…”
Section: Introductionmentioning
confidence: 77%
“…Toward a better understanding of TEC response during geomagnetic storms, TEC modeling during storm conditions is of utmost importance for ionospheric studies and satellite applications. Different TEC models have long been developed and applied for ionospheric studies during both geomagnetically quiet and disturbed conditions (e.g., Chen et al, 2015;Dabbakuti & Ratnam, 2016Ercha et al, 2012Ercha et al, , 2015Feng et al, 2016;Habarulema et al, 2007Habarulema et al, , 2010Habarulema et al, , 2011Hajra et al, 2016;Kakinami et al, 2009;Li et al, 2016;Mao et al, 2005Mao et al, , 2008Mukhtarov et al, 2013;Uwamahoro & Habarulema, 2015;Watthanasangmechai et al, 2012). Findings about the performance of climatological models such as the International Reference Ionosphere (IRI) have shown that, on average, TEC is predicted quite well during geomagnetically quiet conditions although for some cases, IRI model underestimates or overestimates TEC magnitude (e.g., Adewale et al, 2011;Akala et al, 2013;Kenpankho et al, 2011;Rathore et al, 2015).…”
Section: Introductionmentioning
confidence: 99%